How Nigeria Deals with Environmental Damages? An Environmental Legal Perspective - Sylvanus Abila (Journal of Law and Legal Reform, 2021)
The paper carries out a review of the environmental problems associated with atmospheric pollution, air quality emissions and applicable control mechanisms in the detection and evaluation in the Niger Delta region of Nigeria in the light of global trends and best practices given the magnitude of gas flaring taking place in Nigeria’s Niger Delta daily. This is flowing from the findings that gas flaring continues to be a major health hazard to humanity, domestic and global environment. Also considered are the Challenges facing air quality and carbon management in Nigeria and the place of the ongoing National Space Research and Development Agency (NASRDA) funded research on air quality and carbon management and the recent release of the twin regulations of: the Flare Gas (Prevention Of Waste And Pollution) Regulations, 2018 and the Nigerian Gas Flare Commercialization Programme (NGFCP) by the Federal Government Of Nigeria aimed at stopping gas flares in the year, 2020. The paper adopts an admixture of the historical, comparative, the law and development and empirical approaches in appropriate cases.